2010
DOI: 10.1099/mic.0.033936-0
|View full text |Cite
|
Sign up to set email alerts
|

A role for the Rcs phosphorelay in regulating expression of plant cell wall degrading enzymes in Pectobacterium carotovorum subsp. carotovorum

Abstract: The Rcs phosphorelay is a signal transduction system that influences the virulence phenotype of several pathogenic bacteria. In the plant pathogen Pectobacterium carotovorum subsp. carotovorum (Pcc) the response regulator of the Rcs phosphorelay, RcsB, represses expression of plant cell wall degrading enzymes (PCWDE) and motility. The focus of this study was to identify genes directly regulated by the binding of RcsB that also regulate expression of PCWDE genes in Pcc. RcsB-binding sites within the regulatory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 56 publications
1
25
0
1
Order By: Relevance
“…The halo diameters of degraded substrates indicated that the global exoenzyme activities were restored in the opgG rcsC2, opgG rcsC, opgG rcsB, and opgG ⌬rcsCBD double mutant strains compared to the opgG single mutant strain, while activities observed for the corresponding single rcs mutant strains remained unaffected compared to the wild-type strain (Table 4). Thus, in D. dadantii, activation of the RcsCD-RcsB phosphorelay represses exoenzyme synthesis, as observed with Pectobacterium carotovorum (2).…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…The halo diameters of degraded substrates indicated that the global exoenzyme activities were restored in the opgG rcsC2, opgG rcsC, opgG rcsB, and opgG ⌬rcsCBD double mutant strains compared to the opgG single mutant strain, while activities observed for the corresponding single rcs mutant strains remained unaffected compared to the wild-type strain (Table 4). Thus, in D. dadantii, activation of the RcsCD-RcsB phosphorelay represses exoenzyme synthesis, as observed with Pectobacterium carotovorum (2).…”
Section: Resultsmentioning
confidence: 87%
“…The RcsCD-RcsB phosphorelay was first identified in E. coli as a positive regulator of exopolysaccharide synthesis (27). Further studies demonstrated the role of this phosphorelay in regulation of motility, cell division, and virulence in various enterobacterial species, such as E. coli, Salmonella enterica, and P. carotovorum (2,8,19,20,28,31). In D. dadantii, this phosphorelay also controls these cellular processes.…”
Section: Discussionmentioning
confidence: 99%
“…Esta infección se genera debido a que la bacteria produce PCWDEs, o factores de virulencia, como son pectinasas (pectatoliasa, pectinoliasa, peptinometilesterasa y poligalacturonasa), celulasas (CelZ y Y; CeIV y S) y proteasas (aportan aminoácidos para biosíntesis o degradan proteínas asociadas con la resistencia) (11,14), dependientes de oxí-geno, niveles de hierro, nitrógeno, temperatura, osmolaridad, fase de crecimiento, regulación por catabolitos, la activación de proteínas Rc asociadas a sistemas de transducción de señales, niveles de productos de degradación (por medio de un sistema de retroalimentación) entre otros.…”
Section: Pudrición Blanda De La Papaunclassified
“…Intriguingly, in P.w, motility and PCWDE production are coregulated: the master regulator FlhDC of flagellar genes is also implicated in regulation of PCWDE production (Cui et al, 2008;Chatterjee et al, 2009). In addition, we have previously demonstrated that both PCWDE synthesis and motility are regulated by the Rcs phosphorelay (Andresen et al, 2007). The Rcs phosphorelay negatively affects PCWDE expression by inhibiting the expression of flhDC and rsmB (Andresen et al, 2010).…”
Section: Introductionmentioning
confidence: 99%